The Female Perspective : Women Resistance Memory Agency and Some Things Hidden : Highlights of the Female Perspective programme 2017/2018 - Folkersma, Nina (Amsterdam : Castrum Peregrini, 2017)
Bauwens, Lietje ; Amouzou, Hélène ; Blake, Alexis ; Blokland, Sara ; Hershman Leeson, Lynn ; Ivanova, Zhana ; van Manen, Bertien ; Markus, Charlott ; Moulton, Shana ; Otten, Femmy ; Ottenhof, Marijn ; Smith, Cauleen ; Suter, Batia
Some Things Hidden, Castum Peregrini, 18 - 26 November 2017 ; Framer Framed, 18 Jan-11 March 2018
boek